Pengalaman Bullying dan Dampaknya terhadap Konsep Diri Anak dengan Disleksia di Sekolah Umum - Santa Maria Br Saragih; Sri Nurhayati Selian (Jurnal Ilmiah Dan Karya Mahasiswa, 2026)
Children with Special Needs often encounter difficult situations within the school environment. In addition to adjusting to the learning process, they frequently face negative stigma and bullying that affect their psychological well-being and academic abilities. This study seeks to provide a deeper depiction of the social experiences of Children with Special Needs, including how bullying emerges, the factors that trigger it, and the impacts it produces. The approach used is a qualitative method through a literature review of various sources relevant to inclusive education and issues of stigma toward Children with Special Needs. The findings reveal that bullying and other forms of discrimination generally arise due to the school community’s limited understanding of the specific needs of these children, especially those with conditions such as dyslexia or other challenges that influence learning processes. The lack of school support, non-inclusive attitudes, and existing stereotypes further worsen their situation. This study emphasizes the importance of improving teachers’ competencies, providing accurate information to students and parents, and establishing school policies that are more inclusive and supportive of diversity so that Children with Special Needs can develop without being hindered by stigma or bullying.